P2Y12 Inhibition Suppresses Proinflammatory Platelet–Monocyte Interactions - Rolling, Christina C.; Sowa, Marcin A.; Wang, Tricia T.; Cornwell, MacIntosh; Myndzar, Khrystyna; Schwartz, Tamar; El Bannoudi, Hanane; Buyon, Jill; Barrett, Tessa J.; Berger, Jeffrey S. (Thrombosis and Haemostasis, 2023)
Background Monocyte–platelet aggregates (MPAs) represent the crossroads between thrombosis and inflammation, and targeting this axis may suppress thromboinflammation. While antiplatelet therapy (APT) reduces platelet–platelet aggregation and thrombosis, its effects on MPA and platelet effector properties on monocytes are uncertain.Objectives To analyze the effect of platelets on monocyte activation and APT on MPA and platelet-induced monocyte activation.Methods Agonist-stimulated whole blood was incubated in the presence of P-selectin, PSGL1, PAR1, P2Y12, GP IIb/IIIa, and COX-1 inhibitors and assessed for platelet and monocyte activity via flow cytometry. RNA-Seq of monocytes incubated with platelets was used to identify platelet-induced monocyte transcripts and was validated by RT-qPCR in monocyte-PR co-incubation ± APT.Results Consistent with a proinflammatory platelet effector role, MPAs were increased in patients with COVID-19. RNA-Seq revealed a thromboinflammatory monocyte transcriptome upon incubation with platelets. Monocytes aggregated to platelets expressed higher CD40 and tissue factor than monocytes without platelets (p < 0.05 for each). Inhibition with P-selectin (85% reduction) and PSGL1 (87% reduction) led to a robust decrease in MPA. P2Y12 and PAR1 inhibition lowered MPA formation (30 and 21% reduction, p < 0.05, respectively) and decreased monocyte CD40 and TF expression, while GP IIb/IIIa and COX1 inhibition had no effect. Pretreatment of platelets with P2Y12 inhibitors reduced the expression of platelet-mediated monocyte transcription of proinflammatory SOCS3 and OSM.Conclusions Platelets skew monocytes toward a proinflammatory phenotype. Among traditional APTs, P2Y12 inhibition attenuates platelet-induced monocyte activation.
Keywords: aspirin; monocytes; antiplatelet therapy; platelet activation; thromboinflammation